4 SIGNATURES - Ervan Perdana; Stefanny Irawan (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study is accomplished to assist the readers of the graphic novel project that is created to understand more about the elements in the graphic novel 4 Signatures. The purpose of this graphic novel is to educate people about the psychological aspects, what cause it and the results, and to support those who have similar psychological problem.Using the theory of Revenge and Child Abuse, this graphic novel will show the story and the attitudes of the main character cause by psychological problems. The awful result whether it is emotional, verbal, or physical done toward other people by the character helps the readers to understand more of what to do to someone with similar psychological problem and to avoid such psychological problems.